Optimisation of torsional vibration system for a heavy-duty inline six-cylinder diesel engine. (September 2019) - Karimaei, H; Mehrgou, M; Chamani, HR
Torsional vibration is one of the major issues and very important calculation for the safe running of heavy-duty diesel engines, specifically crankshaft. Because of different applications of a heavy-duty diesel engine, different driven machine and different attaching systems are inevitable that affect the torsional system. The cranktrain contains the flywheel and torsional damper. The properties of these parts have significant effect on torsional vibration of the system as well as the crankshaft strength. Initial selection of these properties is usually specified based on engine designer experience and also the torsional vibration calculation of the cranktrain. In this paper, the focus is to find the optimum and reliable operating points for the elements in cranktrain using computer-aided engineering (CAE) tools. These are parameters like tuned mass inertia, flywheel inertia, damper stiffness, damper inertia, damper damping, coupling damping and coupling stiffness. The effect of these parameters on system design criteria, especially crankshaft life, was investigated. The results show high sensitivity of crankshaft safety factor to parameters like tuned mass inertia, damper damping coefficient and damper stiffness. Therefore, damper selection is the most important factor to increase the crankshaft life. The new contribution is that the parameters related to the whole cranktrain system that have the greatest effect were obtained and an optimisation was executed on these parameters to fulfil the vibration targets as well crankshaft life.